Legal Implications of Corruption Crime Legal Process on the Arbitration Dispute Resolution Proceedings - Novian, Desri; Manthovani, Kelly (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
The research aims to analyze allegations of criminal acts of corruption that may affect the validity of arbitration agreements, as well as the implications of investigating or prosecuting these criminal acts simultaneously with arbitration proceedings. The research method relies on arbitration legal instruments and relevant literature, including the New York Convention 1958, the UNCITRAL Model Law, and Law No. 30 of 1999. The research identifies differences in regulations concerning the conduct that arbitrators or arbitral tribunals may adopt when examining arbitration disputes where the subject matter is also under investigation for criminal acts of corruption. The uniqueness or novelty of the research lies in its comprehensive analysis of the legal gaps and uncertainties that arise when these two legal processes run in parallel. The findings show that in some jurisdictions, arbitration disputes related to criminal acts of corruption are refused or rejected, while others continue the arbitration process by considering the principles of party autonomy and separateness in arbitration law. The research recommends several approaches that arbitrators or arbitral tribunals may take and emphasizes the need for regulations from relevant authorities to ensure legal certainty in the parallel examination of arbitration disputes and criminal acts of corruption involving the same subject matter.